Sound intensity mapping of two stroke engine by using hemispherical surface coordinate arrangement - M. S. M., Sani; M. A. F. A., Rahimi; Danial, Mohamed (IOP Publishing, 2019)
This paper presents to investigate the noise source identification of two stroke engine for different engine speed and different general case in two stroke engine without rear cover, with rear cover, with rear cover (composite fibre), and with rear cover (acoustic foam). The experiment carried out utilizing by sound intensity in hemispherical surface arrangement and sound intensity mapping method for engine speed at range 800 to 4800 revolution per minute (rpm). A single module of microphone is used to identify sound power level in hemispherical surface coordinate arrangement while a pair microphone in sound intensity mapping. This method can be applied on-site rather than in an anechoic chamber as long as the background noises are stationary. The sound power level is within 73.7 dB to 81.3 dB in the range of engine speed. The noise level is increasing with engine speed. Rear cover should be applied in order to reduce the sound power level. The project delivers the reliable input for the engineering practice to reduce engine noise level.